Influence of surfactant on the release of propolis from ionomeric cements modified in different time periods - Samara Tonholo Medeiros; Stéfane Edne Souza; Vinícius de Magalhães Barros; Ricardo Rodrigues Vaz; Vagner Rodrigues Santos; Walison Arthuso Vasconcellos (Faculdade Meridional IMED, 2019)
Objective: The objective of this study was to evaluate in vitro the influence of a surfactant on the release of propolis from a modified ionomeric cement at different periods. Methods: Twenty test specimens were made with propolis modified glass ionomer powder. To obtain the modified powder, 20% of green propolis (Propolis Pharmanéctar - Belo Horizonte - MG) was incorporated into the powder of the glass ionomer, and then homogenized. The modified powder and the liquid of the ionomer were used in group A, and in group B, in addition to the modified powder, the liquid was added a surfactant (50% alcohol). As a negative control, specimens were prepared without the presence of propolis, and as a positive control the pure propolis. The release was measured at 1h, 2h, 4h, 24h, 7 days, 15 days and 30 days using a spectrophotometer. Measurements were performed at 300nm length, and the results were submitted to analysis of variance and Tukey's test (p = 0.05). Results: The results indicated that the release was significantly higher at 24 hours (mean of 166.6μg for group A and 118.9μg for group B) and 7 days (Group A: 134.4μg; Group B: 168μg); when compared to the other periods studied. Conclusion: The release of propolis varied significantly as a function of the release time, with propolis release peaks in the periods of 24 hours and 7 days. The use of a surfactant solution altered the release pattern without altering the final amount of propolis released.